X-ray magnetic circular dichroism in Co₂FeGa: First-principles calculations - Kukusta, D.A.; Antonov, V.N.; Yaresko, A.N. (Физика низких температур, 2011)
The electronic structure and x-ray magnetic circular dichroism (XMCD) spectra of the Heusler alloy Co₂FeGa were investigated theoretically from first principles, using the fully relativistic Dirac linear MT-orbital (LMTO) band structure method. Densities of valence states, orbital and spin magnetic moments are analyzed and discussed. The origin of the XMCD spectra in the Co₂FeGa compound is examined. The calculated results are compared with available experimental data.